2019
DOI: 10.3390/molecules24010148
|View full text |Cite
|
Sign up to set email alerts
|

The In Vitro Protective Role of Bovine Lactoferrin on Intestinal Epithelial Barrier

Abstract: The intestinal epithelial barrier plays a key protective role in the gut lumen. Bovine lactoferrin (bLF) has been reported to improve the intestinal epithelial barrier function, but its impact on tight junction (TJ) proteins has been rarely described. Human intestinal epithelial crypt cells (HIECs) were more similar to those in the human small intestine, compared with the well-established Caco-2 cells. Accordingly, both HIECs and Caco-2 cells were investigated in this study to determine the effects of bioactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 63 publications
0
48
0
Order By: Relevance
“…Lactoferrin is an iron binding glycoprotein (80 kDa) present in human colostrum and BC, although levels in BC are only about 10% of human values [ 58 , 59 ]. Lactoferrin induces multiple effects, including enhancing iron absorption as well as possessing antimicrobial activity [ 60 , 61 ], binding lipopolysaccharide, immune-modulating, and stimulating growth of intestinal epithelial cells and fibroblasts [ 62 ]. These findings suggest lactoferrin in BC may be relevant for the regulation of gut growth in neonates.…”
Section: Constituents Of Bcmentioning
confidence: 99%
“…Lactoferrin is an iron binding glycoprotein (80 kDa) present in human colostrum and BC, although levels in BC are only about 10% of human values [ 58 , 59 ]. Lactoferrin induces multiple effects, including enhancing iron absorption as well as possessing antimicrobial activity [ 60 , 61 ], binding lipopolysaccharide, immune-modulating, and stimulating growth of intestinal epithelial cells and fibroblasts [ 62 ]. These findings suggest lactoferrin in BC may be relevant for the regulation of gut growth in neonates.…”
Section: Constituents Of Bcmentioning
confidence: 99%
“…These pathologies are characterized by a loss of barrier integrity and inflammatory processes [203]. Intestinal barrier integrity is a key feature in the health of humans, especially for newborns, because the neonatal immature gastrointestinal system and immune system are still developing [204].…”
Section: Lactoferrin Against Aseptic and Septic Inflammatory Bowelmentioning
confidence: 99%
“…The protective function of bLf in aseptic IBD has been reported in some in vitro and in vivo approaches. In a recent in vitro study, Zhao et al [203] have demonstrated that bLf triggers the up-regulation of claudin-1, occludin, and zonula occludens-1 expression, which, in turn, strengthen the barrier function of intestinal cells. Interestingly, the decrease of TNF-α mRNA levels, in a bLf dose-dependent manner (50 µg/mL and 100 µg/mL), and the consequent inhibition of NF-κB signal pathway were also observed [203].…”
Section: Lactoferrin Against Aseptic and Septic Inflammatory Bowelmentioning
confidence: 99%
See 1 more Smart Citation
“…The protective function of bLf towards intestinal barrier dysfunctions has been reported in two in vitro studies [ 236 , 237 ]. The study by Hering and colleagues demonstrated that bLf was able to: (i) restore TJ morphometry and inhibit apoptosis in TNF-α challenged human epithelial cell models; (ii) counteract trans-epithelial resistance drop and claudin-8 down-regulation in Y. enterocolitica infected human epithelial cell models [ 236 ].…”
Section: Inflammatory Bowel Diseases (Ibds) and Colorectal Cancer mentioning
confidence: 99%